Kontribusi Kepemimpinan, Fasilitas Dan Motivasi Kerja Terhadap Kinerja Guru SMP Negeri 2 Ngaringan Kabupaten Grobogan Tahun Pelajaran 2016/2017 - , Nuryanto; , Dr.Suyatmini,SE.,M.Si; , Dr. Sumardi.M.Si (2017)
The purpose of this research is 1) analyze the contribution of school leadership on teacher performance 2) analyze the school facilitiess on teacher performance 3) analyzing the teachers working motivation on teacher performence 4) analyze the contribution of school leadership, Facilities and motivation, to the performance of teachers.This research uses quantitative research and design. The population in this study are all teachers SMPN 2 Grobogan Ngaringan totaling 40 orang.Teknik analysis used data using multiple linear regression equation.Results of the study 1) there is a contribution to the performance of school leadership teacher at SMPN 2 Grobogan Ngaringan, with t value of 3.483 (p <0.05) so that the research hypothesis is accepted. 2) there is a contribution to the performance of school facilities teacher at SMPN 2 Grobogan Ngaringan, with t value of 4.603 (p <0.05) so that the research hypothesis is accepted. 3) there is a contribution of work motivation on teacher performance in SMPN 2 Grobogan Ngaringan, with t value of 4.207 (p <0.05) so that the research hypothesis is accepted. 4) there is a contribution of school leadership, school facilities and work motivation on teacher performance F value of 101.697 (p <0.05) so that the research hypothesis is accepted. The coefficient of determination of school leadership, school facilities and working motivation simultas on teacher performance amounted to 88.6%.